Orosipon Kan Bikolnon: Interrupting the Nation - Barbaza, Raniela (Archīum Ateneo, 2024)
If narration points to notions of fixity in terms of the position of the narrator and the subsequent structuring of events, orosipon, a Bikolnon word for “story,” suggests a refusal to fixity both in terms of the location of the narrator and the structure itself of the story: the story never stops being formed as it passes through multiple speakers. Orosipon, coming from the root word osip which approximates the verb “tell,” points to more than one person involved in an act of telling, which makes the act of telling proper to no one in particular: indeed, it is improper for any one to act as the sole teller. Orosipon suggests a multiplicity and fluidity that is prohibited by the homogenizing structuring of narration and community. Orosipon reminds us that any speaking necessarily entails a hearing, which is another instance of speaking as well. That is, orosipon points to the structural relationality of speaking which thus necessarily prohibits absolute control. This preliminary study follows the logic of orosipon in reading Valerio Zuñiga’s short story “An Sacong Aginaldo” published in the December 20, 1939 issue of the newspaper An Parabareta. Taking American colonialism and Tagalog nationalism as two stories in the process of being narrated during the period, the study reads the story as an instance of hearing-speaking, or of the insistence of the logic of orosipon itself.